Antibiotic Susceptibility Patterns of Gram-negative Moderately Halophilic Bacteria Isolated from Salted Skins - (:unkn) unknown (SOC LEATHER TECHNOL CHEMISTS, 2020)
Antimicrobial activities of 16 different antibiotics against 47 Gram-negative bacteria isolated from salted skin samples were examined by Kirby-Bauer disc diffusion method. In the present study 10 strains isolated from 6 salted goatskin samples belonging to Russia, South Africa, Bulgaria, Australia, and 37 strains isolated from 14 salted sheepskin samples belonging to Greece, Australia, Bulgaria, South Africa, Israel, USA, Turkey were used as test strains. Susceptibilities of Halomonas venusta, Halomonas zhanjiangensis, Chromohalobacter beijerinckii, Halomonas alkaliphila, Halomonas eurihalina, Chromohalobacter israelensis, Halomonas halodenitrificans, Halomonas halmophila, Chromohalobacter canadensis, Chromohalobacter japonicus, Idiomarina loihiensis against amikacin, gentamicin, tobramycin, cefadroxil were not detected. In addition, susceptibilities of Halomonas eurihalina, Chromohalobacter israelensis and Chromohalobacter beijerinckii against sulfamethoxazole-trimethoprim and ampicillin; aztreonam and ampicillin; ampicillin-sulbactam and ampicillin were not observed, respectively. Although inhibition zones of Halomonas halodenitrificans (15-20mm), Halomonas halmophila (10-15mm), Chromohalobacter japonicus (22-23mm), Idiomarina loihiensis (15mm) against ampicillin were detected, the other strains did not show any inhibition zones. All test strains were susceptible to the other antibiotics such as chloramphenicol, meropenem, imipenem, cefoxitin, cefuroxime, ceftriaxone, amoxycillin/clavulanic acid and piperacillin/tazobactam. All strains except Halomonas eurihalina were found to be susceptible to sulfamethoxazole-trimethoprim. The experimental results of this study demonstrated that 38%, 36%, 26% of the Gramnegative bacterial species isolated from salted sheep and goat skins were resistant against 31%, 25%, 38% of the antibiotics tested. Therefore, effective antibacterial applications should be applied in curing salt to kill multidrug resistant moderately halophilic Gram-negative bacterial species in leather industry.
Keywords: SP NOV.; HALOMONAS-ISRAELENSIS; SHEEP SKINS; CHROMOHALOBACTER; IDENTIFICATION; HALOTOLERANT; CANADENSIS